Between the Formal and the Hidden: Teachers’ and Students’ Narratives of Curriculum Integration, Religious Values, and Character Development in Indonesian Madrasah - Nasyiatul Lailiyah; Siti Aisah; Ahmad Halid; Abu Aman Siddiq Al Ghafar; Nadhliyah Alfin Rochmati (International Journal of Educational Narratives, 2026)
Background. The integration of the curriculum of Islamic boarding schools and madrassas is an important issue in Islamic education, especially in an effort to balance academic achievement and the formation of religious character. Hidden curriculum has been recognized as a potential mechanism for achieving these educational goals. Purpose. This study aims to analyze the contribution of the integration of the pesantren curriculum through the hidden curriculum to students’ academic achievement and religious character formation at MA Miftahul Ulum Lumajang. Method. This study employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving purposively selected informants, including madrasah heads, teachers, students, and pesantren administrators. The data were analyzed using Miles and Huberman’s interactive model. Results. The findings reveal that MA Miftahul Ulum implements an Integrated Tricurriculum Model that combines formal, non-formal, and hidden curriculum. The hidden curriculum plays a significant role in integrating educational practices and fostering both academic achievement and students’ religious character through various implicit learning experiences embedded in daily school and boarding school activities. Conclusion. This study confirms that hidden curriculum not only plays a role in character formation, but also becomes a key mechanism in curriculum integration that has an impact on academic achievement. These findings provide important implications for the development of a more holistic and contextual Islamic education curriculum.